2020
DOI: 10.1177/0020872820941032
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Prolonged Grief Disorder and the role of social work

Abstract: The death rate that we are seeing from COVID-19 is unimaginable, with experts predicting the pandemic will ultimately claim hundreds of thousands of lives. The death toll has already far exceeded the total population of renown cities such as Miami, USA or Canberra, Australia. Behind each death listed as a statistic, there is a social network of family and friends who will be profoundly impacted by the loss. The usual funerals, rituals and customs that occur after a death are now the new casualty of the virus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 8 publications
4
40
0
1
Order By: Relevance
“…The results show the perception of social workers of their relevant role for families and friends in alleviating the impact of the death of loved ones, for instance, in analyzing resilience [56]. This finding resonates with previous evidence about the psychological interventions to alleviate potential prolonged grief disorder [36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results show the perception of social workers of their relevant role for families and friends in alleviating the impact of the death of loved ones, for instance, in analyzing resilience [56]. This finding resonates with previous evidence about the psychological interventions to alleviate potential prolonged grief disorder [36].…”
Section: Discussionsupporting
confidence: 85%
“…The organizational responses of social workers to the pandemic include very diverse actions, managing challenging situations such as contacting through video calls COVID-19 patients with their loved ones in the last moments. Concerning pre-death and post-death preparedness and organization of social workers, it is important to consider their relevant role to provide psychological interventions to alleviate potential prolonged grief disorder in the pandemic context [36]. Volunteers and civil society associations have supported social workers´tasks.…”
Section: Organizational Responses Of Social Workers In the Frontlinementioning
confidence: 99%
“…For example, Mortazavi et al (2020) described the impact of social distancing and isolation in Iran, relating this particular phenomenon to a potentiallyincreased prevalence of complicated grief. Quite a few writers have focused on CIVID-19 changes in burial/funeral practices, often describing the governmental policies that determine these, and suggesting how they may affect the grieving process and adaptation (e.g., Aguiar et al, 2020;Burrell & Selman, 2020;Johns et al, 2020;Mayland et al, 2020;O'Mahony, 2020). On the one hand, there are reality-confronting possibilities (of corona as well as mortality), on the other hand, the situation may lead to avoidance.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have raised concerns that the circumstances of COVID-19 related deaths will lead to a worldwide elevated prevalence of PGD cases (8,9). First, COVID-19 related deaths are usually unexpected, and the unexpectedness of death yielded higher levels of prolonged grief symptoms in Australian (10), Dutch (11), Japanese (12), Chinese (13), and Thai (14) bereaved individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consensus that mental health professionals should pay attention to the rise of prolonged grief disorder after the COVID-19 pandemic (8,9) and call for evidence-based and culturally sensitive bereavement care for individuals bereaved during the pandemic (19)(20)(21)(22)(23)(24), no study speci cally focused on bereaved people and the impact that a death linked to a pandemic had on their subsequent grief before the COVID-19 (25). One recent empirical study included 49 Dutch individuals who experienced COVID-19 related bereavement showed that they reported more severe grief than people who experienced natural losses and equivalent levels of grief with people who experienced unnatural losses (26).…”
Section: Introductionmentioning
confidence: 99%